Optimalisasi Kompetensi Menulis Ilmiah Mahasiswa dengan Metode Metaanalisis - Rahmawati, Laili Etika; Prayitno, Harun Joko; Utami, Dyah Ayu Fajar; Beauty, Melati (Paedagogie, 2019)
This study aims to improve students' writing competence with the meta-analysis method. The research method applied in this study is classroom action research (CAR). The objects of this study were 138 students of the Faculty of Language and Literature Education Study Program Proposal Seminar FKIP, Muhammadiyah University, Surakarta. This research was conducted in the academic year 2018/2019. The results of this study indicate that the meta-analysis method is effective for improving students' scientific writing competence. The effectiveness of the meta-analysis method is shown by the following indicators: (1) the topic of proposed scientific writing is interesting and contains contemporary elements; (2) the presentation of a clear problem statement; reference sources used are actual and factual. Improvement of students' scientific writing competence from initial conditions: cycle 1: cycle 2, which is 75.5: 79.7: 88.9.